Importance of Nucleic Acid Recognition in Inflammation and Autoimmunity - Barrat, Franck J; Elkon, Keith B; Fitzgerald, Katherine A (Annual review of medicine, 2016)
An important concept in immunology is the classification of immune responses as either innate or adaptive, based on whether the antigen receptors are encoded in the germline or generated somatically by gene rearrangement. The innate immune system is an ancient mode of immunity, and by being a first layer in our defense against infectious agents, it is essential for our ability to develop rapid and sustained responses to pathogens. We discuss the importance of nucleic acid recognition by the innate immune system to mounting an appropriate immune response to pathogens and also how inflammation driven by uncontrolled recognition of self-nucleic acids can lead to autoimmune diseases. We also summarize current efforts to either harness the immune system using agonists of nucleic acid-specific innate sensors or, on the contrary, by using inhibitors in autoimmune situations.